Effect of composition on chain dimensions of styrene-methylmethacrylate random copolymers under theta condition - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2011)
Rotational-isomeric-state (RIS)-Metropolis Monte Carlo simulations are performed on poly(styrene-ran-methylmethacrylate) random copolymers to study the intrinsic unperturbed (theta-condition) dimensions. Mean-squared end-to-end distance (< r(2)>(o)), mean-squared radius of gyration (< s(2)>(o)), and characteristic ratio (C(n)) have been calculated for these copolymers constituted by different overall chemical compositions (styrene fractions 0.29, 0.56, and 0.70). Calculations were carried out with chains of 500 repeating units. With an increase in the styrene content there is an increase in (< r(2)>(o)), `, and C(n), in agreement with experimental observations. An increase in the fraction of trans conformational states in the backbone torsion angles is found to be responsible for the exhibited chain expansion behavior. The dimensions calculated by the Monte Carlo simulations agree well with experimental values reported in the literature.
Keywords: chain dimensions; Monte Carlo; poly(methyl methacrylate); Polystyrene; random copolymer; theta conditions